Role of serum CXCL9 and CXCL13 in predicting infection after kidney transplant: A STROBE study. Issue 11 (19th March 2021) - Yan, Lin; Li, Ya-Mei; Li, Yi; Bai, Yang-Juan; Wan, Zheng-Li; Fan, Ji-Wen; Luo, Li-Mei; Wang, Lan-Lan; Shi, Yun-Ying
Abstract : Abstract: Chemokines are majorly involved in inflammatory and immune responses. The interferon-γ-inducible chemokines C-X-C motif chemokines 9 and 10 (CXCL9 and CXCL10) are considerably associated with Th1 cells and monocytes, and their expression levels rapidly increase during the early episodes of renal allograft rejection and various infectious diseases. CXCL13 is one of the most potent B-cell and T follicular helper-cell chemoattractants. The expression of CXCL13 in the presence of infection indicates an important chemotactic activity in multiple infectious diseases. C-C motif chemokine ligand 2 (CCL2) can attract monocytes and macrophages during inflammatory responses. However, there are no studies on the role of these chemokines in posttransplant infection in kidney transplant recipients. In this study, CXCL9, CXCL10, CXCL13, and CCL2 were analyzed using the Bio-Plex suspension array system before transplant and 30 days after transplant. The serum levels of CXCL9 and CXCL13 30 days after kidney transplant were associated with infection within 1 year after transplant ( P  = .021 and P  = .002, respectively). The serum levels of CXCL9 and CXCL13 before surgery and those of CCL2 and CXCL10 before and after surgery were not associated with infection within 1 year after transplant ( P  > .05). The combination of postoperative day (POD) 30 CXCL9 and postoperative day 30 CXCL13 provided the best results with an area under the curve of 0.721 (95% confidence interval, 0.591–0.852), with a sensitivity of 71.4% and specificity of 68.5% at the optimal cutoff value of 52.72 pg/mL. As important chemokines, CXCL9 and CXCL13 could be used to predict the occurrence of infection after kidney transplant. Abstract : Supplemental Digital Content is available in the text